A Phase II Randomized Study of Subcutaneous Ixekizumab, an Anti–Interleukin‐17 Monoclonal Antibody, in Rheumatoid Arthritis Patients Who Were Naive to Biologic Agents or Had an Inadequate Response to Tumor Necrosis Factor Inhibitors1. Issue 7 (July 2014) - Genovese, Mark C.; Greenwald, Maria; Cho, Chul‐Soo; Berman, Alberto; Jin, Ling; Cameron, Gregory S.; Benichou, Olivier; Xie, Li; Braun, Daniel; Berclaz, Pierre‐Yves; Banerjee, Subhashis
<x xml:space="preserve">Abstract</x> Objective To evaluate ixekizumab, an anti–interleukin‐17A (anti–IL‐17A) monoclonal antibody, in 2 populations of rheumatoid arthritis (RA) patients: biologics‐naive patients and patients with an inadequate response to tumor necrosis factor (TNF) inhibitors. Methods In this phase II, randomized, double‐blind study, placebo or ixekizumab was administered subcutaneously to 260 biologics‐naive patients and 188 patients with an inadequate response to TNF inhibitors at weeks 0, 1, 2, 4, 6, 8, and 10 with concomitant disease‐modifying antirheumatic drugs. The primary objective was to determine the dose‐response relationship of ixekizumab as measured by the proportion of biologics‐naive patients meeting the American College of Rheumatology 20% improvement criteria (ACR20) at week 12. Results Using a logistic regression model defined a priori, a statistically significant dose‐response relationship as measured by ACR20 response rates at week 12 was detected in biologics‐naive patients (P = 0.031). For patients with an inadequate response to TNF inhibitors, ACR20 responses at week 12 were significantly better with ixekizumab than placebo (P < 0.05). Decreases in the Disease Activity Score in 28 joints using the C‐reactive protein level (DAS28‐CRP), Clinical Disease Activity Index (CDAI), and CRP level from baseline were observed at week 12 in the ixekizumab groups in both populations (P < 0.05 versus placebo). Onset of action was rapid in some dose groups in both populations, with improvements in the ACR20, DAS28‐CRP, CRP levels, and CDAI observed by day 3 (P < 0.05). Adverse events occurred with similar frequencies overall in the ixekizumab and placebo groups. Infections were more frequent with ixekizumab than placebo (biologics‐naive 25% versus 19%; inadequate responders to TNF inhibitors 27% versus 25%). No mycobacterial or invasive fungal infections were reported. Conclusion Ixekizumab improved RA signs and symptoms in RA patients who were either naive to biologics treatment or had an inadequate response to TNF inhibitors. The safety profile was similar to that of other biologic agents, with no unexpected safety concerns.